Quality control of the breast ca treatments on HDR brachytherapy with TLD-100 (2014)
An anthropomorphic Phantom, a female trunk, was built with a natural bone structure and experimental material coated, glycerin and waterbased material called JJT to build soft tissue equivalent to the muscle of human tissue, and a polymer (styrofoam) to build the lung as critical organ to simulate the treatment of breast cancer, with high dose rate brachytherapy (HDR) and sources of Ir-192. The treatments were planned and calculated for the critical organ: Lung, and injury of 2 cm in diameter in breast with MicroSelectron HDR system and the software Plato Brachytherapy V 14.1 of the Nucletron (Netherlands) which uses the standard protocol of radiotherapy for brachytherapy treatments. The dose experimentally measured with dosimeters TLD-100 LIF: Mg; Ti, which were previously calibrated, were placed in the same positions and bodies mentioned above, with less than 5% uncertainty. The reading dosimeters was carried out in a Harshaw TLD 4500.The results obtained for calculated treatments, using the standard simulator, and the experimental with TLD-100, show a high concordance, as they are on average a § 1.1% making process becomes in a quality control of this type of treatments.